Dynamic contrast enhanced perfusion CT imaging: A diagnostic biomarker tool for survival prediction of tumour response to antiangiogenetic treatment in patients with advanced HCC lesions. Issue 106 (September 2018) - Ippolito, Davide; Querques, Giulia; Okolicsanyi, Stefano; Talei Franzesi, Cammillo; Pecorelli, Anna; Lombardi, Sophie; Orsini, Eleonora; Strazzabosco, Mario; Sironi, Sandro
Abstract: Purpose: To investigate whether perfusion-CT (p-CT) imaging could depict the inhibition of tumor neoangiogenesis induced by Sorafenib in advanced hepatocellular carcinoma (HCC), and whether it could be useful in predicting survival during treatment. Materials and methods: Ninety-eight p-CT examinations were performed among 29 cirrhotic patients, with advanced HCC, before and every 2 months after Sorafenib administration, on a 256-slice MDCT scanner. Perfusion parameters were considered and statistically compared, at baseline and follow-up, between non-progressor (complete response, stable disease or partial response) and progressor (progressive disease) group. Kaplan-Meier analyses estimated the time-to-survival in overall population, after stratifying patients according to mRECIST. Results: The group that responded to Sorafenib showed a significant reduction of values in HCC target lesions after anti-angiogenic therapy ( p  < 0.01), in comparison with progressor group that demonstrated an increase or no significant variation. When patients were stratified into mRECIST, higher survival rate was observed in the non-progressor group compared to the progressor (48.6% vs 28.6%), and statistically significant correlation (p=0.01) was found between percentage variation of perfusion parameters, from baseline to follow-up, and overall survival rate. Conclusion: Quantitative analysis of perfusion parameters, represents prognostic indicators useful in assessment of response to anti-angiogenic therapy, allowing for optimization of individualized treatment.